Penerapan Mirror Therapy untuk Mengatasi Gangguan Mobilitas Fisik pada Lansia dengan Kasus Stroke Non-Hemoragik : Application of Mirror Therapy to Overcome Physical Mobility Disorders in the Elderly with Non-Hemorrhagic Stroke Cases - Yuwono, Dian Kurniasari; Sandagang, Windy Syafitri; Dg.Mangemba; Nurarifah, Nurarifah; Sukmawati, Sukmawati; Galenso, Nitro; Hasan, Sri Musriniawati; Mangundap, Selvi Alfrida; Umar, Nurlailah (Lentora Nursing Journal, 2025)
Background: According to the Indonesian Health Survey, 35.4% of people between the ages of 65 and 74 had a stroke. A non-pharmacological technique called "mirror therapy" uses the cerebral cortex's mirror neuron system to assist stroke victims recover. Purpose: This study aims to investigate the use of mirror therapy in older adults who have had non-hemorrhagic stroke. Method: A case study design of a single elderly patient in the Simpong Health Center area who suffered a non-hemorrhagic stroke in February 2025. Physical examinations, interviews, and observation were used to gather data, which were then processed and presented using a nursing care method. Results: The patient experienced headaches, dizziness when walking 8 meters, trouble sleeping, and frequent awakenings. He also had trouble using his left limbs. blood pressure 173/97 mmHg, rotational movement ability 90 degrees, and upper left extremity’s muscle strength is 3. Ineffective cerebral perfusion, decreased physical mobility, and irregular sleep patterns are among the nursing diagnosis. Vital sign monitoring, medication instruction, mobilization help using mirror therapy twice daily for 30 minutes for five days, and sleep support were among the therapies offered. Upper left extremity’s muscle strength increased by 4 with 180-degree rotating movements on the sixth day of examination. In conclusion, older adults who have had a non-hemorrhagic stroke may benefit from using mirror therapy to strengthen their muscles. Further research is needed to explore the effectiveness of this method on a wider scale